Two views of an inevitable catastrophe that did not take place: Werner Herzog and Daniel Maximin on Guadeloupe, 1976 - Stacey, J (Taylor and Francis, 2019)
This article interrogates the mechanics of catastrophe narration. Rather than doing so through the examination of a celebrated histor- ical orfictional catastrophe, it takes two responses to a catastrophe which did not, in the end, take place: the 1976 non-eruption of the volcano La Soufrière on Guadeloupe. Thefirst is Werner Herzog’sLa Soufrièrewhich, from an outsider’s perspective, stages fascination and disappointment on behalf of a global audience. The second, Guadeloupian author Daniel Maximin’s1987novelSoufrières,uses multiple narrative strands to represent the non-eruption, and thus unlock a longer history of local and global colonial and postcolonial violence. The fact that there was, in fact, no spectacular climax to the events of 1976 permits a focus on other,“slower”narratives which might have been obscured by clouds of gas and outpourings of lava.